Ninjak. Book 1 - Parker, Jeff, 1966- (2021)
"OUT OF THE SHADOWS AND INTO THE DAYLIGHT... Colin King is NINJAK, an ex-MI6 superspy who is second to none. There is no target that Colin cannot strike, no mission that he cannot complete. But what happens to the world's greatest secret agent when all of his secrets are exposed? The entire criminal underworld has Ninjak in their sights... How will the undercover operative survive when there's nowhere left to hide?"--Back cover.